Health Education about Stunting Nutrition in Mothers to Weight Stunting Children Aged 2-5 Years - Risa Nurhayati; Rahayu Budi Utami; Ana Amelia Irawan (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Stunting or short is a failed condition to grow in toddler children due to chronic malnutrition, especially in the first 1000 days of life so that the child is too short for his age. Stunting toddlers tend to have low weight for their age. The purpose of this research is to know the influence of health education on stunting nutrition in mothers to the weight of stunting toddlers aged 2-5 years The research design used correlation with cohort experiment approaches. The study was conducted on 10 May-10 June 2020 in Gampeng village Ngluyu Sub-district of Nganjuk. The population and samples of 22 respondents were taken in total sampling. Independent variables were health education on stunting and weight-dependent variables of stunting toddlers. Data is collected using weight scales. Data analysis using Wilcoxon Sign Ranks with α = 0.05. Weight of stunting toddlers before given health education half of which is 11 respondents (50%) In the category of less weight, after health education was mostly 13 respondents (59.1%) In the normal weight category. There was a health education influence on the stunting nutrients to the weight of stunting toddlers obtained the value of ρ-value 0.000 ≤ α, so Ha accepted. Health education is proven to be effective enough to improve the knowledge of mothers so that it can help to change the foster care of the mother in providing nutrition that has a good impact on weight gain in stunting toddlers.